AN ANALYSIS OF CONCEPTUAL METAPHOR DENOTING LOVE IN “JANE EYRE” BY CHARLOTTE BRONTË - Trần Thị Ngọc Tuyết (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
Thanks to the launch of cognitive-linguistic approach to metaphor by Lakoff and Johnson (1980), the interrelationship between conceptual metaphor and literary discourse has been taken into consideration. One effective way to comprehend how conceptual metaphor system works is by investigating the language used in literature. This paper was conducted with the purpose of examining conceptual metaphor of love in the novel “Jane Eyre” by Charlotte Brontë by analyzing 170 metaphorical expressions of love collected and putting them in appropriate categories of three subtypes: structural, orientational and ontological metaphor. The findings of the research suggested that the author of the literary work intended to convey much more than the surface meaning of the words used throughout the novel. The theory of conceptual metaphor, based on the framework introduced by Lakoff and Johnson (1980), Lakoff and Turner (1989) helped to explain the correspondence between a source domain and a target domain, which is LOVE. There were 15 source domains in total: love is a journey, love is a bond, love is magic, love is a war, love is fire, love is light, love is insanity, love is religion, love is heaven, love is a plant, love is a patient, love is an animal, love is a commodity, love is deep, love is rapture. The large number of source domains used to fully understand the concept of love proved the diversity of images the author of the novel had produced in the writing process, with the view to facilitating reading comprehension. Conceptual metaphor of LOVE IS A JOURNEY, LOVE IS A COMMODITY and LOVE IS A RAPTURE were the most pervasive in structural, ontological and orientational conceptual metaphor respectively. It is hoped that the results of this study can be useful for those interested in exploring this field in the future and the research acts as a reliable source about conceptual metaphor for not only Vietnamese learners and teachers of English but also writers who wish to produce a literary work using metaphorical expressions in a more effective way